High Intensity Interval Training (HIIT) as a Potential Countermeasure for Phenotypic Characteristics of Sarcopenia: A Scoping Review - Hayes, Lawrence D.; Elliott, Bradley T.; Yasar, Zerbu; Bampouras, Theodoros M.; Sculthorpe, Nicholas F.; Sanal-Hayes, Nilihan E. M.; Hurst, Christopher (Frontiers in Physiology, 2021)
Background: Sarcopenia is defined as a progressive and generalized loss of skeletal muscle quantity and function associated predominantly with ageing. Physical activity appears the most promising intervention to attenuate sarcopenia, yet physical activity guidelines are rarely met. In recent years high intensity interval training (HIIT) has garnered interested in athletic populations, clinical populations, and general population alike. There is emerging evidence of the efficacy of HIIT in the young old (i.e. seventh decade of life), yet data concerning the oldest old (i.e. ninth decade of life onwards), and those diagnosed with sarcopenic are sparse. Objectives: In this scoping review of the literature, we aggregated information regarding HIIT as a potential intervention to attenuate phenotypic characteristics of sarcopenia. Eligibility criteria: Original investigations concerning the impact of HIIT on muscle function, muscle quantity or quality, and physical performance in older individuals (mean age ≥60 years of age) were considered. Sources of evidence: Five electronic databases (Medline, EMBASE, Web of Science, Scopus, and the Cochrane Central Register of Controlled Trials [CENTRAL]) were searched. Methods: A scoping review was conducted using the Arksey and O'Malley methodological framework (2005). Review selection and characterization were performed by two independent reviewers using pretested forms. Results: Authors reviewed 1063 titles and abstracts for inclusion with 74 selected for full text review. Thirty-two studies were analyzed. Twenty-seven studies had a mean participant age in the 60s, two in the 70s, and three in the 80s. There were 20 studies which examined the effect of HIIT on muscle function, 22 which examined muscle quantity, and 12 which examined physical performance. HIIT was generally effective in improving muscle function and physical performance compared to non-exercised controls, moderate intensity continuous training, or pre-HIIT (study design-dependent), with more ambiguity concerning muscle quantity. Conclusions: Most studies presented herein utilized outcome measures defined by the European Working Group on Sarcopenia in Older People (EWGSOP). However, there are too few studies investigating any form of HIIT in the oldest old (i.e. ≥80 years of age), or those already sarcopenic. Therefore, more intervention studies are needed in this population.